Alagille syndrome: family studies. Issue 4 (April 1995) - Elmslie, F V; Vivian, A J; Gardiner, H; Hall, C; Mowat, A P; Winter, R M
Abstract : Alagille syndrome (AGS) is one of the major forms of chronic liver disease in childhood with severe morbidity and a mortality of 10 to 20%. It is characterised by cholestasis of variable severity with paucity of interlobular bile ducts and anomalies of the cardiovascular system, skeleton, eyes, and face. Previous studies suggest a wide variation in the expression of the disease and a high incidence of new mutations. To determine more accurately the rate of new mutations and to develop criteria for detecting the disorder in parents we systematically investigated parents in 14 families with an affected child. Clinical examination was supplemented by liver function tests, echocardiography, radiographic examination of the spine and forearm, ophthalmological assessment, and chromosome analysis. Six parents had typical anomalies in two or more systems pointing to the presence of autosomal dominant inheritance. Systematic screening of parents for the features defined in this study should improve the accuracy of genetic counselling.